A multi-constrained QoS aware scheduler for class-based IP networks - Sousa, Pedro (2004)
This article presents a novel modular scheduler with powerful semantics able to differentiate simultaneously multiple QoS metrics in class-based IP networks. In opposition to traditional scheduling mechanisms, this scheduler encompasses rate, loss and delay differentiation capabilities in a flexible way. This behaviour stems from new relative and mixed differentiation models able to bound QoS parameters on high sensitive traffic classes. This proposal is an useful contribution to system designers and network engineers aiming at simple, intuitive, easy to configure and effective mechanisms to enhance QoS in IP networks.